1979
DOI: 10.2190/5vkv-hl8n-m9c8-nt7l
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment to Breast Cancer: A Review of Selected Literature

Abstract: The following is a review of the clinical and research literature concerning women's emotional adjustment to the detection of breast cancer and its subsequent management. The review is organized into ten themes which focus on three general areas: 1) women's response to the diagnosis of breast cancer; 2) involvement of spouse, family and professional providers; and 3) the patient's milieu--how it impinges on the course of her treatment and rehabilitation. Also noted is the paucity of systematic research dealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 69 publications
0
18
0
1
Order By: Relevance
“…Breast cancer has been one of the most extensively studied cancers in the psychosocial and rehabilitation literature [8][9][10]. This undoubtedly relates to the high frequency of this neoplasm and the physical and psychosexual impact of the surgical procedures which have been used as primary treat- ment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer has been one of the most extensively studied cancers in the psychosocial and rehabilitation literature [8][9][10]. This undoubtedly relates to the high frequency of this neoplasm and the physical and psychosexual impact of the surgical procedures which have been used as primary treat- ment.…”
Section: Discussionmentioning
confidence: 99%
“…While breast cancer is one of the most frequently investigated neoplasms in the psychosocial literature [8][9][10], the majority of studies have been retrospective and have involved heterogeneous and selected populations. Little information is available for patients or health care providers on the wide variety of rehabilitation problems facing the patient who is recovering from primary breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently acknowledged that a range of individuals contribute to a person's support network, including spouse, family and friends, health professionals and social support groups (Taylor et al, 1986;Dunkel-Schetter, 1984;Wortman, 1984;Lewis andBloom, 1978-1979 Satisfaction was rated by looking at those patients who had used a source and whether they indicated that they would definitely use one (Figure 2). There was clearly a high level of satisfaction for the three most important sources, family, senior registrar and consultant, around 80% appearing satisfied with the support received.…”
Section: Methodsmentioning
confidence: 99%
“…Group psychotherapy is an intervention that has been used to facilitate adjustment to breast cancer for over a quarter of a century (Lewis & Bloom, 1978). Historically, therapies used for women with breast cancer have been a form of cognitive behavioral therapy (CBT) or supportive-expressive group therapy (SEGT) (Leszcz & Goodwin, 1998).…”
mentioning
confidence: 99%